Molecular detection of the powdery mildew resistance genes in winter wheats DH51302 and Shimai 26 - Yun-feng QU; Pei-pei WU; Jing-huang HU; Yong-xing CHEN; Zhan-liang SHI; Dan QIU; Ya-hui LI; Hong-jun ZHANG; Yang ZHOU; Li YANG; Hong-wei LIU; Tong-quan ZHU; et al. (Journal of Integrative Agriculture, 2020)
Resistance to powdery mildew is an important trait of interest in many wheat breeding programs. The information on genes conferring resistance to powdery mildew in wheat cultivars is useful in parental selection. Winter wheat breeding line DH51302 derived from Liangxing 99 and cultivar Shimai 26 derived from Jimai 22 showed identical infection patterns against 13 isolates of Blumeria graminis f. sp. tritici (Bgt) that causes wheat powdery mildew. DH51302 and Shimai 26 were crossed to a powdery mildew susceptible cultivar Zhongzuo 9504 and the F2:3 families were used in molecular localization of the resistance genes. Fourteen polymorphic markers, which were linked to Pm52 from Liangxing 99, were used to establish the genetic linkage maps for the resistance genes PmDH51302 and PmSM26 in DH51302 and Shimai 26, respectively. These genes were placed in the same genetic interval where Pm52 resides. Analysis of gene-linked molecular markers indicated that PmDH51302 and PmSM26 differed from other powdery mildew resistance genes on chromosome arm 2BL, such as Pm6, Pm33, Pm51, MlZec1, MlAB10, and Pm64. Based on the results of reaction patterns to different Bgt isolates and molecular marker localization, together with the pedigree information, DH51302 and Shimai 26 carried the same gene, Pm52, which confers their resistance to powdery mildew.